Burnout and work‐life balance among pediatric cardiologists: A single center experience. (2nd December 2018) - Dasgupta, Soham; Dave, Ishaan; McCracken, Courtney E.; Mohl, Larry; Sachdeva, Ritu; Border, William
Abstract: Background: Physicians are exposed to workplace factors that may result in acute or chronic stress resulting in burnout. This may impact the productivity and result in suboptimal patient care practices. Methods: We surveyed pediatric cardiology attending physicians at our institution to assess their perception of burnout and work‐life balance using the Maslach Burnout Inventory and the Areas of Work‐Life Survey. Results: Forty‐five out of the 50 pediatric cardiology attendings responded to the survey. They were divided into 4 groups: Interventional/Electrophysiology [n = 3], Cardiac Intensive Care/Inpatient [n = 8], Non‐Invasive Imaging [n = 6], and Outpatient [n = 28]. The Maslach Burnout Inventory demonstrated group‐specific scores in the areas of emotional exhaustion, depersonalization, and personal accomplishment that were all significantly better than the general population. However, group‐specific Areas of Work‐Life Survey results demonstrated concerning findings with respect to the perception of work‐life balance. Conclusions: Although the Maslach Burnout Inventory did not demonstrate significant burnout among the attending physicians, the Areas of Work‐Life Survey results demonstrated reduced work engagement, which can impact patient care and lead to burnout in the future. Based on these results, we plan to implement strategies to help increase work engagement and improve overall organizational effectiveness.